Innovation Strategies, Intellectual Capital, and Competitive Advantage in Indonesian Manufacturing Firms - wahyudi, Tri; Bin Bakar , Mohd Hafiz; Soleha, Nurhayati; Arisondha, Edy (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
Abstract Objective – This study aims to examine the effects of green product innovation, R&D investment, and AI adoption on competitive advantage in Indonesian manufacturing firms. It also investigates whether intellectual capital and government support strengthen these relationships. Design/methodology/approach – A quantitative research design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from manufacturing firms in Indonesia to test the direct effects of green product innovation, R&D investment, and AI adoption on competitive advantage, as well as the moderating roles of intellectual capital and government support. Findings – The findings indicate that green product innovation, R&D investment, and AI adoption each exert a positive effect on competitive advantage. Intellectual capital significantly strengthens the effects of green product innovation and R&D investment on competitive advantage, although its moderating effect on AI adoption is not statistically significant. Government support consistently strengthens all three relationships, suggesting that external institutional support plays an important role in enhancing the contribution of internal innovation capabilities to firm competitiveness. Research limitations/implications – This study is limited to manufacturing firms in Indonesia, which may constrain the generalisability of the findings. The study contributes to the strategic management literature by offering an integrated framework that links innovation strategies, intellectual capital, and government support to competitive advantage. Practical implications – Managers should develop integrated innovation strategies supported by intellectual capital, while policymakers should provide targeted incentives and technical support to facilitate innovation adoption. Originality/value – This study provides a comprehensive understanding of how internal resources and external support interact to drive innovation-led competitiveness in an emerging market context.